2012
DOI: 10.1186/1472-6920-12-78
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and health in the curricula of medical schools in Brazil

Abstract: BackgroundAccording to recent surveys, 59% of British medical schools and 90% of US medical schools have courses or content on spirituality and health (S/H). There is little research, however, on the teaching of S/H in medical schools in other countries, such as those in Latin America, Asia, Australia and Africa. The present study seeks to investigate the current status of teaching on S/H in Brazilian medical schools.MethodsAll medical schools in Brazil (private and public) were selected for evaluation, were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
38

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 23 publications
3
70
0
38
Order By: Relevance
“…7 According to recent surveys, 90% of U.S., 59% of British, and 40% of Brazilian medical schools have courses or content on R/S. 62 In mental health care, the Accreditation Council for Graduate Medical Education (ACGME) guidelines underscore the importance of addressing R/S issues in psychiatric training. 63 In fact, a significant number of U.S. psychiatry programs include a mandatory curriculum on R/S.…”
Section: Challenges To Implementationmentioning
confidence: 99%
“…7 According to recent surveys, 90% of U.S., 59% of British, and 40% of Brazilian medical schools have courses or content on R/S. 62 In mental health care, the Accreditation Council for Graduate Medical Education (ACGME) guidelines underscore the importance of addressing R/S issues in psychiatric training. 63 In fact, a significant number of U.S. psychiatry programs include a mandatory curriculum on R/S.…”
Section: Challenges To Implementationmentioning
confidence: 99%
“…Segundo Luccheti et al 8 , num levantamento com 47,4% das escolas médicas brasileiras, apenas 10,4% dos cursos de graduação dispõem de disciplinas dedicadas ao ensino de espiritualidade e saúde. Dos médicos avaliados nesse estudo, apenas 13,7% referiram ter estudado o tema na graduação, fato condizente, portanto, com os achados de Luccheti.…”
Section: Discussionunclassified
“…No Brasil, levantamentos recentes têm indicado opiniões favoráveis de alunos, professores e diretores de faculdades acerca da relevância do tema e sua importância para a formação médica 8,9 . É importante notar que os próprios pacientes desejam, em sua maioria, que o médico esteja aberto ao tema durante a consulta e o inclua na avaliação clínica 10 .…”
Section: Introductionunclassified
“…Possible explanations are the increase interest for this issue throughout the world, particularly in Brazil, where the religions that use ayahuasca in rituals were developed, and the crescent demand to understand the users and the neuropsychiatric effects of this plant 23 . R/S scales were in the third position (revealing some efforts to provide safe measures for these constructs, as noted by a previous systematic review) 24 , followed by Health education in the forth place (showing an attempt to integrate R/S in higher education) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, this content has been included in the curricula of many universities (90% of US medical schools, 59% of British medical schools and 40% in Brazil) 13,14 . In Brazil, a multicenter study with 3,630 medical students showed a large gap between high levels of students' desire to receive training in R/S and the actual low rates of medical training received on the topic 14 .…”
Section: Introductionmentioning
confidence: 99%